2009
DOI: 10.1086/605475
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Interferon and Ribavirin Promote Early Evolution of Nonstructural 5A Protein in Individuals with Hepatitis C Who Demonstrate a Response to Treatment

Abstract: Background Hepatitis C virus (HCV) quasispecies diversity is more likely to affect early viral decline during treatment of hepatitis C than is having human immunodeficiency virus (HIV) infection. We evaluated the influence of HCV therapy on changes in the nonstructural 5A (NS5A) protein. Methods Fifteen patients with HCV genotype 1 infection with or without HIV infection were recruited for the present study, and the decrease in the HCV RNA level was measured at early time points. The evolution of HCV NS5A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Our findings are consistent with previous observations made on patients undergoing anti-HCV therapy that less complexity and lower diversity of HCV quasispecies at the baseline is associated with viral clearance [19,21,37-39]. Therefore, high genetic variability of HCV could be related to the low efficiency of anti-HCV treatment [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous observations made on patients undergoing anti-HCV therapy that less complexity and lower diversity of HCV quasispecies at the baseline is associated with viral clearance [19,21,37-39]. Therefore, high genetic variability of HCV could be related to the low efficiency of anti-HCV treatment [22].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, high genetic variability of HCV could be related to the low efficiency of anti-HCV treatment [22]. Jain et al observed that the initial anti-viral effect of interferon is influenced by the quasispecies composition at the time of treatment initiation, and patients who demonstrated high viral diversity were less likely to respond to treatment [21]. In agreement with the genetic distance and entropy results, the number of viral strains at baseline was lower for SVR patients than NR and ETR patients, showing that quasispecies composition was more homogeneous than other groups of responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on HCV dynamics typically include a small number of patients. 11,21,27,30,33,34,37,[39][40][41][42][52][53][54][55][56][57][58] Despite this limitation, we identified a delayed early HCV kinetics pattern in LT patients that should be further investigated in larger studies before drawing any definitive conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study has examined the difference in viral sequence diversity between patients with different IL28B SNP polymorphism. In a prior study, more patients with lower baseline sequence diversity in HCV NS5A region were able to achieve early viral response [Jain et al, 2009]. In this study, patients with the favorable CC polymorphism at rs12979860 were hypothesized to have lower sequence diversity.…”
Section: Introductionmentioning
confidence: 83%
“…Patients were recruited prospectively from the HIV and Liver Clinics at Parkland Health and Hospital Systems, a teaching hospital associated with UT Southwestern Medical Center. Patient selection criteria have been described previously [Jain et al, 2009]. All patients signed an informed consent, and were anti‐HCV positive, aged 18–65, and had HCV genotype 1 with serum HCV RNA> 1,000 IU/ml by either polymerase chain reaction (PCR) or branched DNA (bDNA) assays.…”
Section: Methodsmentioning
confidence: 99%